THE SUITABILITY OF DIFFERENT STATISTICAL MEASURES TO ASSESS THE STABILITY OF RESISTANCE TO PHYTOPHTHORA INFESTANS (MONT.) DE BARY IN POTATO CULTIVARS IN FIELD CONDITIONS - T. Beata; F. Bogdan; P. Jarosław; M. Dorota; Zimnoch-Guzowska Ewa (Journal of Animal and Plant Sciences, 2017)
This study presents a comparison of several measures of stability applied for rAUDPC (relative area under the disease progress curve) values, which describes the rate of late blight development on plants of 22 cultivars examined in 13 environments. The stability variance (d2i), coefficient of ecovalence (Wi), coefficient of variability (CV), environmental variance (S2Yi), coefficient of regression (bi), nonparametric measures Si(1) and Si(2), and F statistic for the interaction G×E derived from the Sheffe-Caliński mixed model were among stability measures evaluated. The aim of the study was mainly to compare these measures of stability and select the most suitable one. The environmental variance S2Yi and coefficient of regression bi are correlated with genotypic values and provide information of limited value. The coefficient of ecovalence Wi, stability variance d2i and nonparametric measures Si(1) and Si(2) gave very similar results in terms of cultivar rankings. However, in the case of stability variance d2i, the statistically justifiable division between stable and unstable reacting cultivars is enabled.
Keywords: G×E interaction; stability parameters; potato cultivars; resistance to P. infestans